KONFLIK PENGUASAAN TANAH DI MALUKU UTARA: RAKYAT VERSUS PENGUASA DAN PENGUSAHA - Husen Alting (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Conflict of land ownership used to happened between community versus the government and company, related to land release where there is an investation, almost all over the country. All sorts of conflict reason is about the land ownership and the bargain compensation of land released. So many methods and approaches have been conducted to, but still far from expected, and tend to become worst and victimize the community. State as the government is expected to facilitate each party to solve the problem or at least to avoid the conflict happen, but unfortunately, it still happen. It is because in one hand the government need more investation as the income generating, and on the other side the community claim the land as their own. It is needed to reconceptualized of the land owner for the business in the investation for the release of land ownership. One of the alternative suggested is based on the rental MOU in certain period with certain compensation. By this model, the community keep own their land even the the company is ended.Keywords: land rights, land disputes, dispute resolution